Perbaikan Temuan Plant Audit Di PT X Dengan Berpedoman ISO 22000:2005 - Anggara Jaya; I Gede Agus Widyadana (Jurnal Titra, 2018)
PT X is agro industry that engaged in animal feed. This research is shown to help the correction of plant audit invention in PT X with guidance of ISO 22000:2005. The correction of plant audit invention is especially for warehouse department. The result of plant audit invention that founded in warehouse department is ten results in total. Correction of plant audit invention is done by obrserving and doing interview to related parties. Correction is done through SOP replacement, procedure addition, cleaniness, checklist creaction, and suitable right place transfer.